The impact of demographic dynamics on food consumption and its environmental outcomes: Evidence from China - Shaoting Li; Xuan Chen; Yanjun Ren; Thomas Glauben (Journal of Integrative Agriculture, 2024)
With increasing population and changing demographics, food consumption has experienced a significant transition in quantity and quality. However, a dearth of knowledge remains regarding its environmental impacts and how it responds to demographic dynamics, particularly in emerging economies like China. Using the two-stage Quadratic Almost Demand System (QUAIDS) model, this study empirically examines the impact of demographic dynamics on food consumption and its environmental outcomes based on the provincial data from 2000 to 2020 in China. Under various scenarios, according to changes in demographics, we extend our analysis to project the long-term trend of food consumption and its environmental impacts, including greenhouse gas (GHG) emissions, water footprint (WF), and land appropriation (LA). The results reveal that an increase in the proportion of senior people significantly decreases the consumption of grain and livestock meat and increases the consumption of poultry, egg, and aquatic products, particularly for urban residents. Moreover, an increase in the proportion of males in the population leads to higher consumption of poultry and aquatic products. Correspondingly, in the current scenario of an increased aging population and sex ratio, it is anticipated that GHG emissions, WF, and LA are likely to decrease by 1.37, 2.52, and 3.56%, respectively. More importantly, in the scenario adhering to the standards of nutritional intake according to the Dietary Guidelines for Chinese Residents in 2022, GHG emissions, WF, and LA in urban areas would increase by 12.78, 20.94, and 18.32%, respectively. Our findings suggest that changing demographics should be considered when designing policies to mitigate the diet-environment-health trilemma and achieve sustainable food consumption.
Keywords: 630; demographic dynamics; food consumption; environmental impacts; nutrition intakes